A successful treatment of hypercalcemia with zoledronic acid in a 15-year-old boy with acute lymphoblastic leukemia - Park, Hye-Jin (Ann Pediatr Endocrinol Metab, 2016)
Severe hypercalcemia in children is a rare medical emergency. We present a case of a 15-year-old boy with hypercalcemia (total calcium level, 14.2 mg/dL) with a normal complete blood count, no circulating blasts in the peripheral blood film, and no other signs of acute lymphoblastic leukemia (ALL), including no signs of lymphadenopathy or hepatosplenomegaly. The hypercalcemia was successfully treated with zoledronic acid. As hypercalcemia can be the only presenting symptom of ALL in children, the diagnosis is often delayed. In children presenting with hypercalcemia, malignancies must be considered in the differential diagnosis.